Fluids confined in porous media: An ideal gas in different matrices - W.Dong (Condensed Matter Physics, 2007)
At present, a number of models are available describing the adsorption of a fluid in a random porous medium. In this paper, some exact and analytical results are presented. All the results are obtained for an ideal gas adsorbed in various porous matrices. It is shown that the calculations are not always trivial. In some cases of complicated matrices, it is impossible to obtain any analytical results even for an ideal gas.